Twice the sum of 4 and x is less than -16

Answers

Answer 1
Answer: 2(4+x)<-16\n8+2x<-16\n2x<-24\nx<-12
Answer 2
Answer:

Final answer:

The solution to the inequality 'Twice the sum of 4 and x is less than -16' is x < -12.

Explanation:

The given question is asking to solve the inequality 'Twice the sum of 4 and x is less than -16'. Let's break it down step by step:

  1. Twice the sum of 4 and x can be written as 2(4 + x).
  2. Now, we need to express this expression as less than -16, which gives us the following inequality: 2(4 + x) < -16.
  3. We can simplify the inequality by first multiplying 2 with 4 + x to get 8 + 2x, and then we have 8 + 2x < -16.
  4. To isolate the variable x, we subtract 8 from both sides: 2x < -16 - 8, which gives 2x < -24.
  5. Finally, we divide both sides of the inequality by 2 to get x < -12.

Therefore, the solution to the inequality is x < -12.

Learn more about Inequality here:

brainly.com/question/32625151

#SPJ11


Related Questions

The graph of a quadratic function is shown. What is the minimum value of the function? A. 1 B. 2 C. 3 D. -3 E. -2
16,900,000 in scientific notation
Three-toed sloths have four legs. How many toes would 25 sloths have?
A sine function can be used to model light waves. Green light has a wave length, or period of about 520 nm. Which equation best models green light?A.) y=sin 260/pi theta B.) y= sin pi/520 theta C.) y= sin 520/pi theta D.) y= sin pi/260 theta Please help
A bird flies due east for 600 meters at a constant speed of 10 m/s. What is the bird's acceleration? (a) with no change in velocity, there is no acceleration (b) 60 m/s (c) 6 m/s/s (d) 60 m/s/s (e) not enough information is given

[-10 +(-3)]-[6+(-9)] how do you solve this question

Answers

you calculate
[-10 +(-3)]-[6+(-9)]
=[-10-3]-[6-9]
=-13-[-3]
=-13+3
= -10

How do I do number 6?

Answers

2 x^(2) +4x -48 = 0 \n  \n 2( x^(2) +2x-24) = 0 \n  \n 2(x+6)(x-4)=0 \n  \n x_1 = -6 \n x_2 = +4

3x2 − y3 − y3 − z if x = 3, y = −2, and z = −5.

Answers

ok so from experience on this site
3x2=3x^2
people don't know how to put exponents
3x^2-y^3-y^3-z
simplify first

3x^2-2y^3-z

x=3
y=-2
z=-5
3(3^2)-2(-2)^3-(-5)
3(9)-2(-8)+5
27+16+5
48

Evaluate :- a) (6.4)² - (3.6)²

Answers

Answer:28

Step-by-step explanation: 6.4x6.4 = 40.96

3.6x3.6=12.96

Final answer:

To evaluate the expression (6.4)² - (3.6)², square each of the numbers and then subtract the square of 3.6 from the square of 6.4 to give a result of 28.

Explanation:

The question asked is mathematics related and it requires to evaluate an expression: (6.4)² - (3.6)². This is a simple arithmetic problem that involves squaring numbers and subtraction.

Firstly, squaring a number means multiplying the number by itself. Hence, (6.4)² equals to 6.4 * 6.4 which gives 40.96. Similarly, (3.6)² equals to 3.6 * 3.6 which gives 12.96.

Then, subtract the squared number of 3.6 from the squared number of 6.4. That is: 40.96 - 12.96, and you'll have your answer, which is 28.

Learn more about Arithmetic here:

brainly.com/question/35421603

#SPJ11

Mark is building a custom wooden frame around his flower bed. The length of the frame is 5.45 feet and the width of the frame is 3.275 feet.  WHAT IS THE AREA OF THE FLOWER BED WITHOUT ROUNDING ???  ____________ square feet.

Answers

A = lw
A = 5.45 × 3.275
A = 17.84875

The area of the frame (without rounding) is 17.84875.

What are the solutions of the equation x4 – 5x2 – 14 = 0? Use factoring to solve.

Answers

We will use factoring:x^(4) -5 x^(2) -14 = 0 \n  x^(4) -7 x^(2) +2 x^(2) -14 =0 \n  x^(2) ( x^(2) -7)+2( x^(2) -7)=0  \n  ( x^(2) -7)( x^(2) +2)=0
x² - 7 = 0
x² = 7
x = √(7)
or x=-√(7)
x² + 2 = 0
x² = - 2, this part of equation has no solutions.

Answer:

d on edge.

Step-by-step explanation: